2010
DOI: 10.1590/s0100-06832010000600007
|View full text |Cite
|
Sign up to set email alerts
|

Número mínimo de tensões para determinação da curva característica de retenção de água de um latossolo vermelho eutrófico sob sistema de semeadura direta

Abstract: RESUMOPara o conhecimento do comportamento físico-hídrico do solo, é fundamental a determinação da curva de retenção de água (CRA). A aquisição de dados para obtenção da CRA envolve processos demorados e custos elevados. A hipótese deste estudo foi a de que é possível determinar a CRA com menor número de tensões, reduzindo seu tempo de obtenção, sem, contudo, comprometer a acurácia dos resultados. Assim, o objetivo deste trabalho foi determinar quais tensões podem ser utilizadas para determinação da CRA de Lat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
2
0
4

Year Published

2018
2018
2020
2020

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 13 publications
3
2
0
4
Order By: Relevance
“…This result highlights the influence of the residual moisture determination on S-index estimate, corroborated by the observations of Jorge et al (2010) about this moisture. In general, S-index is underestimated when residual moisture is fixed at 0.01 m 3 m -3 , compared with the residual moisture estimated by the fitting.…”
Section: Resultssupporting
confidence: 82%
See 1 more Smart Citation
“…This result highlights the influence of the residual moisture determination on S-index estimate, corroborated by the observations of Jorge et al (2010) about this moisture. In general, S-index is underestimated when residual moisture is fixed at 0.01 m 3 m -3 , compared with the residual moisture estimated by the fitting.…”
Section: Resultssupporting
confidence: 82%
“…Therefore, in the estimation of S-index, it is important that the residual moisture is not fixed because the worst EF values were obtained when it was fixed. Jorge et al (2010) also highlighted the importance of determining the moisture content at 1,500 kPa in the determination of the SWRC and claimed that an erroneous estimate of such moisture content could lead to incorrect results in the fit of the SWRC, as well as in the determination of S-index, emphasizing the importance of determining this moisture content in the estimation of S-index. Asgarzadeh et al (2014) found positive correlation of the S-index with soil available water and integral water capacity, reinforcing the importance of determining residual moisture and saturation moisture, which are extreme points of the SWRC.…”
Section: Resultsmentioning
confidence: 99%
“…Para este trabalho optou-se pelo estudo envolvendo sete combinações diferentes de pontos e tensões (Tabela 3), incluindo a curva de 13 pontos (A1) que foi tomada como referência neste estudo. Jorge et al (2010), coloca como sendo sempre necessária a utilização do ponto de 15.000 hPa ao se utilizar o modelo de van Genuchten para elaboração de uma curva de retenção de água do solo. Caso contrário, segundo o autor é provável que se obtenham resultados incorretos de avaliação da retenção de água e, consequentemente, da disponibilidade de água para as plantas, assim como incertezas na determinação de indicadores da qualidade física do solo derivados da curva de retenção como o índice S proposto por Dexter, (2004).…”
Section: Número De Pontos E Distribuição Na Curva De Retençãounclassified
“…Portanto, excluindo-se o ponto de 15.000 hPa (Tabela 3). Para as demais combinações de pontos de tensão foi mantido o ponto de 15.000 hPa entre as combinações, como proposto por (JORGE et al,2010).…”
Section: Número De Pontos E Distribuição Na Curva De Retençãounclassified
See 1 more Smart Citation